-x-4=3x-52

Simple and best practice solution for -x-4=3x-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-4=3x-52 equation:


Simplifying
-1x + -4 = 3x + -52

Reorder the terms:
-4 + -1x = 3x + -52

Reorder the terms:
-4 + -1x = -52 + 3x

Solving
-4 + -1x = -52 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-4 + -1x + -3x = -52 + 3x + -3x

Combine like terms: -1x + -3x = -4x
-4 + -4x = -52 + 3x + -3x

Combine like terms: 3x + -3x = 0
-4 + -4x = -52 + 0
-4 + -4x = -52

Add '4' to each side of the equation.
-4 + 4 + -4x = -52 + 4

Combine like terms: -4 + 4 = 0
0 + -4x = -52 + 4
-4x = -52 + 4

Combine like terms: -52 + 4 = -48
-4x = -48

Divide each side by '-4'.
x = 12

Simplifying
x = 12

See similar equations:

| -6t+-7=7 | | 2r(0.7+5)= | | 4x+3-8x+1=-5x+9 | | 6(3x+5)-9x=75 | | 12-3y=16-5y | | 3-5=7n+11 | | 2x+7+(2x+6)+2x=2x+(2x)+(3x)+7 | | -20=0.1x-0.5x | | 1/2(2/4) | | 188=32x+10(6) | | 2/3(12-14)=2 | | m+7+8=-28 | | x^3+9x^2+8x+72=0 | | 3(x+7)-3=54 | | 10+5-1-5b=15b+3 | | m+7+8=28 | | .20x+.25(70)=36.5 | | 2=6(2a+2) | | -4x+10=-2x+2 | | -3(2-4x)=18 | | m+4+9=-23 | | m+4+9=23 | | 2/3(-42+49)=2 | | 6x+24=10x-20 | | 6x^2-18x+0=0 | | C=2(8)-2 | | 2(3x+2)=4x+16 | | 5w-6-2w=18 | | 12b-6+2-3b=4b+5 | | 3/8x-1/4 | | m+7=-37 | | 2/3(9-21/2)=2 |

Equations solver categories